Identification of novel nonedible oil seeds via scanning electron microscopy for biodiesel production. Issue 2 (29th October 2019) - Dawood, Sumreen; Ahmad, Mushtaq; Zafar, Muhammad; Ali, Muhammad I.; Ahmad, Khalid; Sultana, Shazia; Usma, Anwer; Nazish, Moona; Butt, Maryam A.; Ozdemir, Fethi A.; Kilic, Omer
Abstract: Exploration of substitute energy feed‐stocks is the much‐debated topic in the scientific society due to increasing power crises and related ecological concerns. As a source of sustainable energy, biodiesel turns out to be the best alternative to petro fuels. In this context, nonedible oil‐producing seeds might be a potential source for biodiesel production owing to their environment‐friendly nature and cost‐effectiveness. The current study, consequently, deals with the investigation and identification of micro‐morphological characters between six novel nonedible oil‐bearing seeds employing scanning electron microscopy as possible biodiesel feed‐stocks. Light microscopic examinations show that seed size varies from 0.3 to 1.3 cm in width and 0.5 to 1.5 cm in. Additionally, a large difference in seed color ranges from dark brown, black, and various shades of light brown was also witnessed. The FFA content of the seeds ranges in 0.3–4.1 mg KOH/g, and the seed oil content fall in 30–65% (w/w) range. SEM‐mediated seed ultrastructure investigations displays greater variation in seed size, shape, color, periclinal wall shape, and sculpturing and so on. All the seeds differ from rounded, ovoid, ovate, oblong, flattened, and elliptical shape. Greater variation in seed wall structure has been seen from angular, entire, irregular, straight, elongated, smooth, and polygonal. The periclinal wall arrangements show alteration from flat, depressed, elevated, smooth, pentagonal, bullate, and coarse seed margins. The results obtained from the current study suggest that scanning electron microscopy could be a beneficial tool in vitalizing the hidden micromorphological characters among various nonedible oil producing seeds, which eventually helps in exploration, correct identification, seed classification, and authentication in future. Abstract :